2017
DOI: 10.1155/2017/4259183
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Atrial Fibrillation: Factors Associated with Persistence and Risk of Ischemic Stroke

Abstract: Background Atrial fibrillation (AF) is one of the commonest cardiovascular manifestations of thyrotoxicosis. A significant proportion of patients have persistent AF which may have long term consequences, for example, ischemic stroke. Methods We performed a retrospective cohort study in a regional hospital from January 2004 to June 2016 to examine the clinical characteristics and outcomes of thyrotoxic patients who presented with atrial fibrillation and to investigate possible factors associated with persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 67 publications
1
19
0
6
Order By: Relevance
“…However, the incidence of ischemic stroke is considered to be lower in paroxysmal AF patients than in those with sustained AF [28], and the different types of AF should not change the anticoagulation strategy [8]. In addition, Wong et al reported that hyperthyroid AF patients who had a restored sinus rhythm had a lower incidence of stroke than those with persistent AF [29]. In this study, information on sinus rhythm restoration was lacking.…”
Section: Discussionmentioning
confidence: 82%
“…However, the incidence of ischemic stroke is considered to be lower in paroxysmal AF patients than in those with sustained AF [28], and the different types of AF should not change the anticoagulation strategy [8]. In addition, Wong et al reported that hyperthyroid AF patients who had a restored sinus rhythm had a lower incidence of stroke than those with persistent AF [29]. In this study, information on sinus rhythm restoration was lacking.…”
Section: Discussionmentioning
confidence: 82%
“…Once initiated, AF alters the electrical and structural properties of the atria in a manner that affects its maintenance, increasing the risk of recurrence and can alter the response to antiarrhythmic drugs (97,105). In addition, AF increases the risk of cerebrovascular stroke, peripheral embolization, and overall mortality (106)(107)(108). About 13-15% of individuals with newly developed AF have biochemical hyperthyroidism (103).…”
Section: Cardiac Arrhythmias Associated With Thyroid Hormonesmentioning
confidence: 99%
“…However, in persistent AF patients, this increasing risk trend was nonsignificant. One explanation could be that persistent AF was associated with more advanced atrial structural remodeling and more non‐PV triggers than paroxysmal AF (Wong et al, 2017 ). Thus, thyroid hormone may be less able to modulate arrhythmogenic effects after cryoballoon‐based PVI ablation than in other scenarios (Chen et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%